how can western companies successfully develop a social media strategy in China - Nie, Lanying (2014)
Over the past decade, an internet phenomenon has swept the globe. It has increasingly dominated social and political life online, enabling information to be shared with the world at merely a click, and as a result has become incredibly lucrative to its founders and those entrepreneurs who have utilize it to its full potential. This phenomenon is of course social media. This blog post will thus look to make comparisons between the trends Chinese and Western modern social medial sites and online communities. We will discuss major players in the Chinese social media market and Chinese user characteristics and opportunities for Western companies who wish to venture into the social media market in China or integrate their businesses with social media.